Leveraging Waqf Management to Promote Educational Quality Aligned with SDGs: A Global Review - Anwar Musaddad; Dariyanto; Hari Widyasmoro; Itsna Rusydiana; Muhamad Ibnu Soleh (IQRO: Journal of Islamic Education, 2025)
Waqf is a key tool for socioeconomic development, notably in education. Waqf substantially improves educational quality and is crucial to SDG No. 4. Waqf, including scholarships, endowment funds, educational properties, and academic support, has been established in several countries to improve education. Waqf administration and allocation vary by country due to government policies, social structures, and regional conditions. This study compares waqf implementation in education across nations using a systematic literature review (SLR). This study examines 28 relevant literary sources from 2010 to 2025 using Confidence. This research aims to evaluate waqf implementation in education and find ways to improve its effectiveness in achieving the Sustainable Development Goals, notably in education quality. This comparative study explores optimal waqf management in education and makes policies to improve waqf's role in inclusive and sustainable education. The findings show that waqf collection and distribution can promote education from elementary to higher education.